2017
DOI: 10.1111/jvh.12808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ledipasvir/sofosbuvir on the work productivity of genotype 1 chronic hepatitis C patients in Asia

Abstract: Chronic, untreated hepatitis C virus (HCV) infection is associated with a poor clinical prognosis and a detrimental impact on patients' lives, including on work productivity. To estimate the value of productivity losses due to genotype 1 (GT1) HCV infection in Hong Kong, Singapore, South Korea and Taiwan and to estimate the potential productivity gains associated with treating patients with ledipasvir/sofosbuvir (LDV/SOF) therapy, an economic model was developed with a time horizon of 1 year. Hepatitis C virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The economic analyses described thus far have principally focused on the perspective of the payer—such as national health insurance schemes and private insurers—without taking into account the full value to society of treating CHC patients. A model of work productivity in Hong Kong, Singapore, South Korea and Taiwan showed that treatment of CHC patients with LDV/SOF could lead to annual productivity gains of approximately US$209 million, driven particularly by reduced presenteeism . Furthermore, an analysis from the USA evaluated the ‘value of cure’ in GT1, CHC patients from a broader societal perspective .…”
Section: Economic Aspects Of Hcv Infectionmentioning
confidence: 99%
“…The economic analyses described thus far have principally focused on the perspective of the payer—such as national health insurance schemes and private insurers—without taking into account the full value to society of treating CHC patients. A model of work productivity in Hong Kong, Singapore, South Korea and Taiwan showed that treatment of CHC patients with LDV/SOF could lead to annual productivity gains of approximately US$209 million, driven particularly by reduced presenteeism . Furthermore, an analysis from the USA evaluated the ‘value of cure’ in GT1, CHC patients from a broader societal perspective .…”
Section: Economic Aspects Of Hcv Infectionmentioning
confidence: 99%
“…Furthermore, preliminary estimates from Asian countries suggested similarly enormous productivity losses: $349 million per year in Taiwan, $146 million in South Korea, $17 million in Singapore, and $11 million in Hong Kong (in 2014 US dollars). 107 In contrast, as the studies suggested, curing HCV infection in HCV genotype 1 carriers in the United States only could save up to $2.7 billion over a 1-year time horizon solely owing to an increase in work productivity, 104 and from V340 to V435 million in the 5 European countries cited. 105 Additionally, in Asian countries, treatment with alloral interferon-free regimens would presumably result in the productivity gains of $138 million, $58.7 million, $6.8 million, and $4.5 million in Taiwan, Korea, Singapore, and Hong Kong, respectively.…”
Section: Economic Burden Of Hepatitis C Infectionmentioning
confidence: 87%
“…105 Additionally, in Asian countries, treatment with alloral interferon-free regimens would presumably result in the productivity gains of $138 million, $58.7 million, $6.8 million, and $4.5 million in Taiwan, Korea, Singapore, and Hong Kong, respectively. 107 Notably, in those studies, the savings were projected to come from improved presenteeism only, because the short-term data available to the authors did not suggest any improvement in absenteeism; thus, those estimates might increase with longer follow-up of cured patients. It is, however, important to note that calculated work productivity used self-reports collected by the WPAI:SHP instrument, so the true gain in employers' and society benefits might differ if measured by more objective algorithms.…”
Section: Economic Burden Of Hepatitis C Infectionmentioning
confidence: 98%
“…The indirect economic burden of WP loss in the U.S. has been estimated to be approximately 7.1 billion USD per year while the WP loss from 5 major European countries (France, Germany, Spain, Italy and United Kingdom) has been estimated to be 2.6 billion Euros per year [116,117]. Furthermore, WP loss from Asia (Hong Kong, South Korea, Singapore and Taiwan) has been estimated to be over half a billion dollars per year with treatment resulting in a gain of USD 208.9 million per year [118].…”
Section: Economic Burden Of Hcv-related Liver Diseasementioning
confidence: 96%